O Efeito da Manipulação Miofascial sobre o Limiar Doloroso em Atletas Durante Período Competitivo - Costa, Natalia Ancioto da [UNESP]; Poggetto, Simone Franco Dal [UNESP]; Pedroni, Cristiane Rodrigues [UNESP] (My University, 2012)
Introduction: The myofascial pain syndrome (SDM) is one of the most common causes of musculoskeletal pain. One of the possible treatments for SDM is the type of physiotherapy myofascial manipulation. Objective: This study aimed to analyze the effect of manipulative technique with myofascial pain threshold before and after applying the technique in athletes during competition period. Methods: Participated in the study 62 subjects of both genders, aged between 14 and 38 (19.64 + 4.89), who had myofascial pain syndrome, 32 oh the treatment group and 30 divided equally between control group and the placebo group. All were athletes and operated by the Department of Sport and Leisure in the city of Marilia – SP and were in competitive period. The volunteers were evaluated according to their musculoskeletal symptoms to prove the necessity of performing the technique of myofascial manipulation. Confi rmed the need to assess the pressure pain threshold (LDP) using a digital dynamometer. After the measurement, patients underwent treatment or using the technique of myofascial manipulation, or a sliding surface for the placebo or no treatment for the control group followed by the immediate reassessment of the LDP. Results: The results were normalized by Kolmogrov-Smirnov test (KS). Through the ANOVA test found no differences between the initial LDP thresholds between groups. To compare pre and post LDP of the three groups we used the paired t test. Signifi cant difference (p=0.0001) between the values of pain threshold before and after application of myofascial manipulation for the treated group and not signifi cant for the control group (p=0.45) and placebo (p=0.16). Conclusion: We conclude then that the myofascial manipulation technique is able to increase pain threshold after micro-musculoskeletal injuries in athletes in competitive period.

Introdução: A síndrome dolorosa miofascial (SDM) é uma das causas mais comuns de dor músculo esquelética. Um dos possíveis tratamentos para a SDM é a técnica fi sioterapêutica de manipulação miofascial. Objetivo: O presente estudo teve como fi nalidade analisar o efeito da técnica de manipulação miofascial com o limiar de dor pré e pós a aplicação da técnica em atletas durante período de competição. Método: Participaram da pesquisa 62 sujeitos de ambos os gêneros, com idades entre 14 e 38 anos (19,64 ± 4,89), que apresentavam síndrome dolorosa miofascial, sendo 32 do grupo de tratamento e 30 divididos igualmente entre grupo controle e grupo placebo. Todos eram atletas e atuavam pela Secretaria de Esporte e Lazer da cidade de Marília - SP e encontravam-se em período competitivo. Os voluntários foram avaliados de acordo com sua sintomatologia musculoesquelética para comprovação da necessidade de realização da técnica de manipulação miofascial. Confi rmada a necessidade, avaliava-se o limiar de dor por pressão (LDP) utilizando um Dinamômetro Manual Digital. Após a mensuração, realizava-se ou o tratamento utilizando a técnica de manipulação miofascial, ou um deslizamento superfi cial para o grupo placebo, ou nenhum tratamento para o grupo controle seguido da reavaliação do LDP imediato. Resultados: Os resultados foram normalizados pelo teste Kolmogrov-Smirnov (KS). Por meio do teste ANOVA não foram encontradas diferenças entre os limiares de LDP iniciais entre os grupos. Para comparação dos valores de pré e pós LDP dos três grupos foi utilizado o teste t pareado. Foi encontrada diferença signifi cativa (p= 0, 0001) entre os valores de limiar doloroso pré e pós aplicação de manipulação miofascial para o grupo tratado e não signifi cativa para os grupos controle (p=0,45) e placebo (p=0,16). Conclusão: Conclui-se, então que a técnica de manipulação miofascial é capaz de aumentar limiar doloroso após microtraumatismos musculoesqueléticos em atletas em período competitivo.
The effect of myofascial manipulation on the pain threshold in athletes during competitive period.
Keywords: atletas; sindrome da dor miofascial; Dor